Molecular basis of carotid body tumor and associated clinical features in Japan identified by genomic, immunohistochemical, and clinical analyses. Issue 4 (14th January 2023) - Yoshihama, Keisuke; Mutai, Hideki; Sekimizu, Mariko; Ito, Fumihiro; Saito, Shin; Nakamura, Shintaro; Mikoshiba, Takuya; Nagai, Ryoto; Takebayashi, Akiko; Miya, Fuyuki; Kosaki, Kenjiro; Ozawa, Hiroyuki; et al.
Abstract: Carotid body tumor (CBT) is classified as a paraganglioma (PGL). Here, we report the genetic background, protein expression pattern, and clinical findings of 30 Japanese CBT cases. Germline pathogenic or likely pathogenic (P/LP) variants of genes encoding succinate dehydrogenase subunits ( SDHs ) were detected in 15 of 30 cases (50%). The SDHB variants were the most frequently detected, followed by SDHA and SDHD variants. One case with SDHAF2 variant was bilateral CBT, and other two multiple PGL cases were not detected P/LP variants. The three cases with germline variants that could be tested did not have somatic P/LP variants of the same genes. Immunohistochemical analysis showed negative SDHB signals in CBT tissues in five cases with germline P/LP variants of SDHB, SDHD, or SDHA . In addition, SDHB signals in CBT tissues were negative in four of nine cases without germline P/LP variants of SDHs . These findings suggest the involvement of unidentified molecular mechanisms affecting SDHs . Abstract : Germline pathogenic or likely pathogenic (P/LP) variants of genes encoding succinate dehydrogenase subunits ( SDHs ) were detected in 15 of 30 cases (50%). The SDHB variants were the most frequently detected, followed by SDHA, SDHD, and SDHAF2 .